2023
DOI: 10.3390/antiox12091704
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cytotoxic Potential of Carlina vulgaris Extract and Bioactivity-Guided Isolation of Cytotoxic Components

Ireneusz Sowa,
Roman Paduch,
Jarosław Mołdoch
et al.

Abstract: Carlina vulgaris is a poorly understood plant in the context of biological activity, despite its widespread application in ethnomedicine in numerous European countries. The aim of this study was to assess the cytotoxic potential of the plant against human colorectal adenocarcinoma (HT29) and to isolate the plant components linked to this effect. Ultra-high performance liquid chromatography with a high-resolution/quadrupole time-of-flight mass spectrometer (UHPLC–HR/QTOF/MS–PDA) was used for the phytochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The ferric reducing abilities of the specimens were evaluated based on the method described in the literature [ 42 ]. Each sample was mixed with fresh FRAP reagent, which comprised a mixture of 300 mM acetate buffer at pH 3.6, 10 mM TPTZ dissolved in 40 mM HCl, and 20 mM FeCl 3 ·6H 2 O, with proportions set at 10:1:1.…”
Section: Methodsmentioning
confidence: 99%
“…The ferric reducing abilities of the specimens were evaluated based on the method described in the literature [ 42 ]. Each sample was mixed with fresh FRAP reagent, which comprised a mixture of 300 mM acetate buffer at pH 3.6, 10 mM TPTZ dissolved in 40 mM HCl, and 20 mM FeCl 3 ·6H 2 O, with proportions set at 10:1:1.…”
Section: Methodsmentioning
confidence: 99%
“…Phytochemical research has shown that C. vulgaris , one of the least studied species of the genus, is rich in polyphenols and minerals, especially populations that grow in uncontaminated areas, which contain more chlorogenic acid and exhibit greater antioxidant activity [ 84 ]. It has also been found to have a protective effect against H2O2-induced oxidative stress in human skin fibroblasts [ 85 ] and the antioxidant and cytotoxic potential of C. vulgaris against human colorectal adenocarcinoma has been determined [ 86 ].…”
Section: Informant Consensus Factor (Icf)mentioning
confidence: 99%